A noble scheme - White, Roseanna M. (White, Roseanna M. Imposters, 2024)
"As part of England's most elite private investigation firm, Gemma and Graham must set aside their broken relationship to work together on a new case. Graham is determined to use this opportunity to win back the only woman he's ever loved, but there's no guarantee Gemma's shattered heart can be restored"--